Efektifitas Penggunaan Aplikasi berbasis Android Sebagai Dampak dari Penyebaran Covid-19 - Natalia Tri Astuti; Agus Wilson (JURNAL EDUSCIENCE (JES), 2021)
The background of this research is distance learning which utilizes media in the form of android-based applications in connection with the global covid-19 pandemic experienced by various countries, one of which is Indonesia. This condition affects the movement of various sectors, including the education sector. After going through several months with this global pandemic condition, with all teaching-learning activities from various levels carried out from home, the use of appropriate methods is a very serious concern. Learning from home is one way that is expected to be able to suppress the spread of covid-19. Many distance learning media are available, so it is necessary to know the effectiveness of using these media to be used in distance learning. The method used in this research was qualitative-quantitative with a sample of 30 students chosen at random with the student record "technology literate". The data collection method was carried out through a questionnaire using electronic media and internet networks. The results of this research indicate that not all android-based applications can be used effectively in distance learning. This research is expected to provide new views and references on the effectiveness of the use of electronic media in learning, so as to increase the effectiveness of distance learning for various levels of Education. Key Words: Distance learning, electronic media, covid-19